2023
DOI: 10.1097/md.0000000000033622
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pre-fracture proximal femur geometry on hip fracture type in elderly patients

Abstract: This study aimed to analyze the relationship between fracture type by determining data on the geometry of the proximal femur in the pre-fracture period in patients over 65 years of age who had hip fractures as a result of low-energy trauma. A total of 127 patients who were admitted to the hospital for reasons other than hip pathology within 1 year before the occurrence of hip fracture and who had an anterior-posterior pelvic X-ray were included in the study. Measurements were made to evaluate the proximal femu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…This remark is supported by authors that examined the BMD in the femoral neck region [56,57]. The parameter of the FND has been a subject of doubt among authors, as certain studies suggest that shorter values are associated with FTF [21,44], while others with FNF [11,43]. Lastly, our study did not prove any important association between the FND values and type of hip fracture.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…This remark is supported by authors that examined the BMD in the femoral neck region [56,57]. The parameter of the FND has been a subject of doubt among authors, as certain studies suggest that shorter values are associated with FTF [21,44], while others with FNF [11,43]. Lastly, our study did not prove any important association between the FND values and type of hip fracture.…”
Section: Discussionsupporting
confidence: 78%
“…In accordance with the previous mentioned assumption, in the event of a lateral fall, it is observed that the lateral area of the proximal femur comes into contact with the periphery of the acetabulum, which in this particular scenario, exhibits a more lateralized position. The force applied to sustain the hip under such circumstances could plausibly result in a FTF [43]. However, within our study sample, we did not manage to establish this association, as no statistically significant difference was observed between the groups.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations